First report of the presence of L1014S Knockdown-resistance mutation in Anopheles gambiae s.s and Anopheles coluzzii from Togo, West Africa - Djègbè, Innocent (Wellcome Open Res, 2018)
Background: To optimize the success of insecticide-based malaria control intervention, knowledge of the distribution of Anopheles gambiae species and insecticide resistance mechanisms is necessary. This paper reported an updated data on pyrethroids/DDT resistance in the An. gambiae s.l population from Togo.  Methods: From December 2013 to April 2015, females of indoor-resting An. gambiae s.l were captured in three locations belonging to three different ecological zones. Resistance to DDT, permethrin and deltamethrin was screened in F1 progeny of collected mosquitoes using WHO susceptibility tests. The identification of species of An. gambiae complex and the detection of kdr and ace.1 (R) allele were carried out using DNA-based molecular techniques. Results: An. gambiae from Kovié and Nangbéto were highly resistant to DDT and permethrin with mortalities rate ranging from 0.83% to 1.58% for DDT and zero to 8.54% for permethrin. Mosquitoes collected in Nangbéto displayed 81.53% mortality with deltamethrin. An. coluzzii and An. gambiae s.s were found in sympatry in Nangbéto and Mango . The allelic frequency of L1014F was high, ranging from 66 to 100% in both An. coluzzii and An. gambiae s.s. For the first time we detected the L1014S allele in both An. coluzzii and An. gambiae s.s. from Togo at the frequency ranging from 5% to 13% in all the sites. The kdr N1575Y was present at various frequencies in both species ranging from 10% to 45%. Both An. gambiae s.s. and An. coluzzii shared the ace1 (R) mutation in all investigated sites with allelic frequency ranging from 4% to 16%. Conclusion: These results showed that multiple mutations are involved in insecticides resistance in An. gambiae populations from Togo including the kdr L1014F, L1014S, and N1575Y and ace.1 (R) G119S mutations.